PERANCANGAN MEDIA KOMUNIKASI VISUAL BUKU ILUSTRASI SEJARAH PURA MERU DAN MASJID NURUL FALAH DI CAKRANEGARA - nyoman miyarta yasa (Institut Agama Hindu Negeri Gde Pudja Mataram, 2026)
This study examines the limited availability of engaging visual teaching materials based on local history to instill the value of tolerance in elementary school students in the multicultural environment of SDN 20 Cakranegara, Lombok. Amidst the dominance of global entertainment media, local symbols such as Pura Meru and Masjid Nurul Falah, which are rich in the values ​​of interfaith harmony, have not been optimally explored as sources of character education. The main objective is to design visual communication media in the form of illustrated books on the history of the two holy sites along with supporting products (t-shirts, tote bags, mugs, stickers) for students aged 7–12 years. The descriptive qualitative method applies a design thinking approach through the stages of empathize, define, ideate, prototype, and test, with primary data collection via interviews with teachers and religious leaders, field observations, and documentation. The results of trials on students and teachers show the effectiveness of the book in increasing understanding of the value of tolerance, with visual design and layout that are appropriate to children's learning characteristics and the Merdeka Curriculum. This research contribution complements the study of educational visual communication design, provides a replicable model for multicultural education in Indonesia's diverse religious areas, and emphasizes the urgency of strengthening the character of tolerance from an early age.